Moderate Level of Genetic Diversity in Anthocephalus Macrophyllus Roxb, an Endemic Tree of Sulawesi and Its Implication in Conservation - Siti Halimah Larekeng; Muh. Restu; Gusmiaty Gusmiaty; Syamsuddin Millang; Budirman Bachtiar (Hasanuddin University, 2018)
Anthocephalus macrophyllus Roxb is an endemic tree to Sulawesi having high economic value. It has rarely been investigated, either in genetic population or genetic consevation aspects. The information regarding genetic diversity is very important in order to gain more understanding for breeding and conservation strategies. Genetic diversity is used as material selection of expected genotype. The study was to determine genetic diversity of A. macrophyllus from Sulawesi provenances that would be used in further development of this species. Leaf samples were collected from 108 families of A. macrophyllus belong to Sulawesi provenances. Four out of ten microsatellite markers that had high polymorphism were used for amplifying the 108 DNA samples. Results showed number of allele and mean of allele were 3 to 4 alleles and 3,5, respectively. Moreover, PIC mean of the evaluated loci was 3,7. The analysis of genetic relationship showed that the 108 families had moderate level of genetic diversity. This research suggest to establish germplasm nursery via either seed from different provenance. In situ and ex situ approaches have to be applied together for conserving genetic resources of Anthocephalus macrophyllus.